2019
DOI: 10.1080/17461391.2019.1694079
|View full text |Cite
|
Sign up to set email alerts
|

Cheater, cheater, pumpkin eater: the Dark Triad, attitudes towards doping, and cheating behaviour among athletes

Abstract: We examined the relationships between the Dark Triad personality traits (Machiavellianism, narcissism, and psychopathy), attitudes towards doping, and cheating behavior among athletes. One-hundred and sixty-four athletes completed a questionnaire that assessed the Dark Triad and their attitudes towards doping. Following this, athletes completed a matrix solving task within a specific time limit. Participants were told they would receive a financial reward for the total number matrices they could solve, but onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Other scholarly activity has revealed that other personality factors are associated with doping attitudes such as perfectionism ( Madigan et al, 2016 ), risk-taking propensity ( Jalleh et al, 2014 ), and honesty and humility ( Nicholls et al, 2019a ). Further, doping attitudes have also been associated with a taxonomy of personality traits, the Dark triads ( Nicholls et al, 2017c , 2019b ). It appears that personality may play an important role in shaping attitudes toward doping, so the SDCM and the SDCM-AA may need revising as other research identifies personality factors and alternative taxonomies of personality traits that are associated with doping attitudes and doping susceptibility.…”
Section: Limitationsmentioning
confidence: 99%
“…Other scholarly activity has revealed that other personality factors are associated with doping attitudes such as perfectionism ( Madigan et al, 2016 ), risk-taking propensity ( Jalleh et al, 2014 ), and honesty and humility ( Nicholls et al, 2019a ). Further, doping attitudes have also been associated with a taxonomy of personality traits, the Dark triads ( Nicholls et al, 2017c , 2019b ). It appears that personality may play an important role in shaping attitudes toward doping, so the SDCM and the SDCM-AA may need revising as other research identifies personality factors and alternative taxonomies of personality traits that are associated with doping attitudes and doping susceptibility.…”
Section: Limitationsmentioning
confidence: 99%
“…Therefore, narcissism may be not as important to doping compared to Machiavellianism and psychopathy. Recently Nicholls et al (2019) re-examined the relationship between the Dark Triad and attitudes towards doping. It was found that all the Dark Triad dimensions were positively correlated with attitudes towards doping and cheating behaviours.…”
Section: Achievement Orientation As a Negative And A Positive Predictmentioning
confidence: 99%
“…The year 2020 has been unprecedented and exceptionally complex, also in the context of anti-doping efforts in situations of considerable restrictions, lockdowns, reduced options for training and competition, and collection and analysis of anti-doping samples. Probably more than ever, understanding an athlete's attitude towards doping, [1][2][3] the susceptibility and motivation(s) to cheat, identifying factors that influence or predict an athlete's (anti-)doping position and behavior, [4][5][6][7][8] and approaches that support strengthening and consolidating highest levels of sportspersonship as well as harm reduction strategies, 9 have been required to effectively limit intentional anti-doping rule violations (ADRVs).…”
Section: Introductionmentioning
confidence: 99%
“…ence or predict an athlete's (anti-)doping position and behavior, [4][5][6][7][8] and approaches that support strengthening and consolidating highest levels of sportspersonship as well as harm reduction strategies, 9 have been required to effectively limit intentional anti-doping rule violations (ADRVs).…”
mentioning
confidence: 99%